Control of Blood Pressure and Anti Hypertensive Drug Profile in End Stage Renal Disease Patients Undergoing Maintenances Hemodialysis: An Observation and a Retrospective Study - Patel, Rishita Darshan; Shah, Nirzarini Nilesh (Indian Journal of Pharmacy Practice)
Introduction: Hypertension is the second leading cause of End Stage Renal Disease after diabetes mellitus. If hypertension is an etiologically significant cardiovascular risk factor in hemodialysis patients, the first step would be to assess the level of BP accurately. To manage hypertension, limiting dietary fluide intake, and individualizing dialysate sodium delivery would be the initial steps as non pharmacological measures. Therefore as a pharmacological measurement, study was conducted to determine control of blood pressure by anti hypertensive drug treatment. Material And Method: Treatment and control of hypertension was assessed retrospectively in a cohort of 100 clinically stable, adult patients undergoing hemodialysis. Frequency and duration of hemodialysis were also assessed. For quality of life, kidney disease outcomes quality initiative-survey form™ 1.3 health survey was used for 40 adult patients undergoing hemodialysis. Results: Hypertension was documented in patients (n=97) with complicated kidney disease (97.16%) and patients (n=85) with non-complicated kidney disease (85.66%). Hypertension was adequately controlled in only 2.83% (n=3) patients with complicated kidney disease and 14.33% patients (n=15) with non complicated kidney disease undergoing maintainanace hemodialysis. Patients with non-diabetic kidney disease had better quality of life as compared to the patients with diabetic kidney disease. Conclusion: Control of hypertension, particularly systolic hypertension, in patients undergoing hemodialysis for prolong period was inadequate, despite recognition of its prevalence and the use of antihypertensive drugs. Optimizing the use of medications and closer attention to non pharmacological interventions, may improve control of BP.
Keywords: Anti hypertensive drugs; Chronic kidney failure; End stage renal disease (ESRD); Hemodialysis; Hypertension; Quality of life